2002
DOI: 10.1097/00007632-200208010-00004
|View full text |Cite
|
Sign up to set email alerts
|

Local Application of Disc-Related Cytokines on Spinal Nerve Roots

Abstract: Based on previous observations and the data of the present study, one may conclude that tumor necrosis factor-alpha from nucleus pulposus cells seems to be intimately involved with the basic pathophysiologic events leading to both nerve root dysfunction and pain after local, epidural application of nucleus pulposus. One may therefore also suspect that pharmacologic inhibition of tumor necrosis factor-alpha may at least theoretically be considered in the clinical situation with disc herniation and sciatica.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(55 citation statements)
references
References 29 publications
1
50
0
4
Order By: Relevance
“…Herniated discs induce sciatica by both mechanical and chemical factors [1,13,15,16,[29][30][31][32]34]. Proinflammatory cytokines, such as tumor necrosis factor-alpha (TNF-a), Interleukin-1-beta (IL-1b), Interleukin-6 (IL-6), and nitric oxide, phospholipase A2, and serotonin, are known chemical inducers of sciatica [1,3,13,14,17,18,22,32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herniated discs induce sciatica by both mechanical and chemical factors [1,13,15,16,[29][30][31][32]34]. Proinflammatory cytokines, such as tumor necrosis factor-alpha (TNF-a), Interleukin-1-beta (IL-1b), Interleukin-6 (IL-6), and nitric oxide, phospholipase A2, and serotonin, are known chemical inducers of sciatica [1,3,13,14,17,18,22,32].…”
Section: Introductionmentioning
confidence: 99%
“…Herniated discs induce sciatica by both mechanical and chemical factors [1,13,15,16,[29][30][31][32]34]. Proinflammatory cytokines, such as tumor necrosis factor-alpha (TNF-a), Interleukin-1-beta (IL-1b), Interleukin-6 (IL-6), and nitric oxide, phospholipase A2, and serotonin, are known chemical inducers of sciatica [1,3,13,14,17,18,22,32]. Nucleus pulposus contains TNF-a, and nucleus pulposus applied to the dorsal root ganglion (DRG) induces pain-related behavior in rats and causes morphological and functional changes in DRG and spinal cord [13,14,26,29,30,32,37,48].…”
Section: Introductionmentioning
confidence: 99%
“…Different structures in the degenerative segment, including the disc (annulus, nucleus pulposus and the cartilaginous end plate), may be involved in the pain generating process, which may be of mechanical and/or biochemical origin, including inflammatory responses mediated through proinflammatory cytokines [2,5,6,7,12,18,20,24,25,26,31].…”
Section: Introductionmentioning
confidence: 99%
“…Proinflammatory cytokine pain mediators like substance P and tumor necrosis factor alpha (TNF-alpha) are released or activated by nervous structures in contact with the nucleus pulposus [2,23]. Substance P acts as a neuroregulator or neurotransmitter in the conduction of nociceptive stimuli, and is a modulator of neuroimmunoregulation.…”
Section: Introductionmentioning
confidence: 99%
“…TNF alpha applied locally on cauda equina of pigs induces allodynia and morphologic changes that mimic human radiculopathy [5]. It was then suggested that anti-TNF drugs could be administered to patients with sciatica of discal origin.…”
Section: Anti-tnf Treatment Of Sciaticamentioning
confidence: 99%